1999
DOI: 10.1063/1.479000
|View full text |Cite
|
Sign up to set email alerts
|

Photofragment energy distributions and dissociation pathways in dimethyl sulfoxide

Abstract: Photolysis of dimethyl sulfoxide in a molecular beam with 210 and 222 nm photons reveals the decomposition mechanism and energy disposal in the products. Using vacuum ultraviolet light and a time-of-flight spectrometer, we identify CH 3 and CH 3 SO as primary fragments and CH 3 and SO as secondary fragments. From CH 3 quantum yield measurements, we find that secondary decomposition is minor for 222 nm photolysis, occurring in only about 10% of the fragments, but it increases to about 30% in the 210 nm photolys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
37
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(50 citation statements)
references
References 29 publications
11
37
2
Order By: Relevance
“…Since the SOCl + transients reflected the temporal evolution of the SOCl intermediate, the 8.7 ps component was consistent with the decay of hot SOCl produced in the stepwise pathway. This assignment was in agreement with the previous studies, which suggested that the photodissociation of SOCl 2 at 235 nm underwent a stepwise dissociation process and produced the fragement of Cl with quite high quantum yield [34,35].…”
Section: Resultssupporting
confidence: 93%
“…Since the SOCl + transients reflected the temporal evolution of the SOCl intermediate, the 8.7 ps component was consistent with the decay of hot SOCl produced in the stepwise pathway. This assignment was in agreement with the previous studies, which suggested that the photodissociation of SOCl 2 at 235 nm underwent a stepwise dissociation process and produced the fragement of Cl with quite high quantum yield [34,35].…”
Section: Resultssupporting
confidence: 93%
“…It may be noted that appearance of spin forbidden transitions due to spinorbit interactions are not unusual in the spectra of [33]. It may be mentioned here that inverted vibrational population distributions for the photodissociated SO fragment have been reported earlier [2,26,27]. In particular for photoexcitation at 193, 210 and 220 nm, population has been found to be maximum in the v″ ¼2, 1 and 1 levels, respectively.…”
Section: High Resolution Studiesmentioning
confidence: 77%
“…Table 6), which is well above the energy required to break the two C-S bonds in (CH 3 ) 2 SO, and results in the formation of the primary products CH 3 and SO [29]. Photodissociation via the electronic σ n 'n and π n 'n transitions at 210 and 222 nm (5.90 and 5.58 eV), respectively, have also been shown to release the primary products CH 3 and SO [2]. It has been established from these experiments [2,4,[26][27][28][29][30]] that most of the other possible fragments require extensive nuclear rearrangements that make their production unlikely.…”
Section: High Resolution Studiesmentioning
confidence: 94%
See 2 more Smart Citations